If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) + (2x + -3y) * i + 4i = 5 Reorder the terms: (2 + x) + (2x + -3y) * i + 4i = 5 Remove parenthesis around (2 + x) 2 + x + (2x + -3y) * i + 4i = 5 Reorder the terms for easier multiplication: 2 + x + i(2x + -3y) + 4i = 5 2 + x + (2x * i + -3y * i) + 4i = 5 2 + x + (2ix + -3iy) + 4i = 5 Reorder the terms: 2 + 4i + 2ix + -3iy + x = 5 Solving 2 + 4i + 2ix + -3iy + x = 5 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 4i + 2ix + -3iy + -2 + x = 5 + -2 Reorder the terms: 2 + -2 + 4i + 2ix + -3iy + x = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 4i + 2ix + -3iy + x = 5 + -2 4i + 2ix + -3iy + x = 5 + -2 Combine like terms: 5 + -2 = 3 4i + 2ix + -3iy + x = 3 Add '-1x' to each side of the equation. 4i + 2ix + -3iy + x + -1x = 3 + -1x Combine like terms: x + -1x = 0 4i + 2ix + -3iy + 0 = 3 + -1x 4i + 2ix + -3iy = 3 + -1x Reorder the terms: -3 + 4i + 2ix + -3iy + x = 3 + -1x + -3 + x Reorder the terms: -3 + 4i + 2ix + -3iy + x = 3 + -3 + -1x + x Combine like terms: 3 + -3 = 0 -3 + 4i + 2ix + -3iy + x = 0 + -1x + x -3 + 4i + 2ix + -3iy + x = -1x + x Combine like terms: -1x + x = 0 -3 + 4i + 2ix + -3iy + x = 0 The solution to this equation could not be determined.
| 4/5f=2/3 | | 6(3s+4)=96 | | (2x+3(x-7))=0 | | 0.25e=8 | | 5(a-6)=75 | | -2(z+4)=44 | | (u-6)*10=100whatisu | | -4q-8=16 | | 5x^8+35x^7+60x^6= | | 10t-20=60 | | (8a-7b)=16a^2b-14ab^2 | | 10+-20=60 | | N-41=20+4 | | -4(c+1)+2c=3(2b-1) | | 4(4y+5)=60+5(y+3) | | x^5-x^4-5x^3-x^2+8x-4=0 | | 4(-5y+1)=-96 | | k.1/3=5 | | 6+8n+2+8n+2= | | 3N+5=40+25 | | X^2-5x+6=6x-18 | | 12b-5-2b=2 | | A(x+2)+B(x-1)-1=0 | | 3x-4+5=x | | 1.5=2/1.7 | | n^3-6*n^2+5*n-324=0 | | 4x+2=3-(5x-6) | | 2m^2-7m=12 | | 3x-4-5=x | | 7(x+1)=-14 | | 17-4x=13+x | | -7xb=b-49 |